POWER LOSS CHARACTERIZATION IN COMPACT GAN TRANSISTOR-BASED SYNCHRONOUS BUCK CONVERTERS FOR AERIAL DRONE APPLICATIONS - BURKOVSKIY, YAROSLAV; ZINKOVSKIY, YURIY (Herald of Khmelnytskyi National University. Technical sciences, 2023)
This article presents a comprehensive analysis of power loss in compact Gallium Nitride (GaN) transistor-based synchronous buck converters, specifically tailored for aerial drone applications (UAV). The study begins by outlining the increasing demand for efficient power management in drones, driven by the need for longer flight times and enhanced performance. The focus then shifts to the utilization of GaN transistors, highlighting their advantages over traditional silicon-based components in terms of efficiency, size, and thermal performance.The core of the research involves an examination of power loss mechanisms in these converters. This includes both conduction and switching losses, with a particular emphasis on how the unique properties of GaN transistors influence these factors. The methodology adopted for this analysis combines theoretical modeling with empirical data.Subsequently, the article delves into the design considerations for optimizing these converters. It discusses the balancing act between minimizing power loss and maintaining other critical parameters, such as size, weight, and cost. Practical strategies for achieving this balance are explored, including circuit design optimizations and the selection of appropriate ancillary components.The findings of this study are significant for engineers and designers in the field of power electronics, particularly those working on aerial drone technology. The solutions provided into the GaN transistor-based synchronous buck converters under real-world conditions offer valuable guidelines for enhancing the efficiency and performance of these systems. Furthermore, the research contributes to the broader understanding of GaN technology in power applications, reinforcing its potential as a superior alternative to traditional silicon solutions.In conclusion, this article not only provides an analysis of the specific area of power loss in GaN-based converters for drones but also underscores the broader implications and benefits of this technology in advancing the capabilities of power electronic systems.
Keywords: synchronous buck converter; gallium nitride; GaN; UAV; power management; calculation